Preparation method of encapsulated metal catalyst for improving tar quality
By encapsulating metal active sites in HZSM-5 molecular sieve, the problem of reducing tar yield caused by metal active sites participating in hydrogen transfer during tar lightening is solved, and the effective tar lightening and hydrogen-rich gases are achieved The utilization improves the quality of tar and the stability of the catalyst.
Patent Information
- Application Number
- CN202411251805.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
Prior Art During the lightening of tar, metal active sites participate in hydrogen transfer lead to a decrease in tar yield and the hydrogen-rich component in the pyrolytic gas cannot be effectively utilized.
Ni@HZSM-5 catalyst was prepared by encapsulation method, and metal active sites were encapsulated in the microporous structure of HZSM-5 molecular sieve, and hydrogen-rich gas was activated by the spatial domain characteristics of the molecular sieve to achieve phase separation of tar cracking and hydrogenation properties. .
Improve the light component content and yield of tar, enhance the activity and stability of the catalyst, effectively utilize the hydrogen source in the pyrolytic gas, avoid metal active components participating in the activation of hydrogen-rich gas, and stabilize the Lightweight components.
Smart Images

Figure CN119114146A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of energy science and technology, and in particular to a method for preparing an encapsulated metal catalyst for improving tar quality. Background Art
[0002] Coal pyrolysis is an important way to utilize coal in a step-by-step manner. It mainly produces coal gas, liquid tar and solid semi-coke. The pyrolysis gas contains a high amount of hydrogen-rich gas, which can be used as urban or industrial gas. Tar hydrogenation can produce a series of clean fuels such as gasoline, diesel, and aviation fuel. Tar also contains substances such as BTEXN, which are important chemical raw materials or products. However, tar contains a large amount of heavy components (parts with a boiling point higher than 360°C), which usually account for more than 50% of the tar composition. These heavy components have certain viscosity and corrosive properties. After tar condenses, it will cause blockage, scaling and corrosion of pipelines or equipment, affecting the long-term stable operation of the equipment system, thereby affecting the industrialization process of the pyrolysis system. In order to realize the in-situ lightening process of tar, the researchers used HZSM-5 molecular sieve as a catalyst, and used the acidity and pore structure of the molecular sieve itself to catalyze the cracking of tar under an inert atmosphere to increase the content of light tar. However, while the tar is lightened, the pyrolysis gas in the system contains a large amount of H 2 , CH 4 Hydrogen-rich components such as Co, Mo and Ni are not fully utilized. Currently, the active components that can be used for hydrogenation include metals such as Co, Mo and Ni. Some researchers use the impregnation method to load metals such as Co, Mo and Ni for the tar upgrading process. The study found that compared with the parent HZSM-5 molecular sieve, although the yield of light components in the tar is increased after the metal is loaded, the yield of tar is seriously reduced. Analyzing the catalyst itself, since the metals loaded by the impregnation method are mostly on the surface and part of the pores of the molecule, the metal active sites participate in the cracking and hydrogenation of the tar during the hydrogen transfer process, accompanied by a large amount of non-condensable gas, and the Ni-based catalyst has the most significant effect. Therefore, this type of loading method cannot effectively utilize the hydrogen-rich components in the pyrolysis gas as a hydrogen source in the tar lightweight process, thereby achieving the lightweight of the tar. Therefore, we need a synthesis method to achieve the separation of the cracking and hydrogenation properties of the tar by the metal active sites during the hydrogen transfer process. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing an encapsulated metal catalyst for improving the quality of tar. The Ni-based catalyst is prepared by an encapsulation method using HZSM-5 molecular sieve as a carrier, which is represented by Ni@HZSM-5. In this way, the metal active sites can be encapsulated inside the molecular sieve. Since the HZSM-5 molecular sieve is a typical microporous structure, the macromolecular components in the tar cannot contact the metal active components, but can activate the H generated in the pyrolysis system. 2 , CH4 etc., thus producing ·H and ·CH x Small molecular free radicals such as tar pyrolysis fragments can be stabilized to further improve the quality of tar and the yield of light oil products.
[0004] To achieve the above object, the present invention provides a method for preparing an encapsulated metal catalyst for improving the quality of tar, wherein metal is used as an active component, an organic complex (3-mercaptopropyl) trimethoxysilane KH-590 is used as a metal protective agent, tetraethyl orthosilicate TEOS is used as a silicon source, and Al 2 (SO 4 ) 3 18H 2 O is an aluminum source, tetrapropylammonium hydroxide TPAOH is used as a template, and the active component is encapsulated in the molecular sieve during the crystallization process of the molecular sieve to prepare an encapsulated metal catalyst, including the following steps:
[0005] Step 1: First, take a certain amount of TPAOH and H 2 O and KH-590 were placed in a beaker and stirred for 8 h. Then a certain concentration of Ni(NO 3 ) 2 6H 2 O solution and continue stirring for 0.5h, then slowly add a certain amount of TEOS to the mixed solution and stir for 13h;
[0006] Step 2: Take a certain amount of TPAOH and H 2 O, NaOH and Al 2 (SO 4 ) 3 18H 2 O is prepared into a transparent solution, and then the prepared transparent solution is slowly added dropwise to the mixed solution in step 1, and then stirred in a water bath at 80°C for 2h to obtain a gel;
[0007] Step 3, after the obtained gel is loaded into an autoclave, it is crystallized in a homogeneous reactor;
[0008] Step 4: centrifuge the catalyst obtained after crystallization to neutrality, dry overnight, and calcine the dried sample in a muffle furnace to obtain a Ni@NaZSM-5 molecular sieve sample;
[0009] Step 5: Prepare NH 4 NO 3 solution, Ni@NaZSM-5 molecular sieve and NH 4 NO 3 The solution was stirred in an oil bath, filtered and washed, and then the same steps were followed again. The obtained catalyst was dried overnight and calcined in a muffle furnace to obtain Ni@HZSM-5 molecular sieve.
[0010] Step 6: The obtained Ni@HZSM-5 molecular sieve is heated to 2 The catalyst was calcined at 700 °C for 2 h under an atmosphere and pressed into tablets. The catalyst was crushed and sieved to obtain the Ni@HZSM-5 molecular sieve catalyst, i.e., an encapsulated metal catalyst.
[0011] Preferably, the mass fraction of the active component metal nickel is 1%-5%.
[0012] Preferably, the active component metal is platinum, nickel, cobalt, molybdenum, etc., and the carrier is a molecular sieve.
[0013] Preferably, the dosage of each component in step 1 is: 10-20 mL of TPAOH, 5-10 mL of H 2 O, 0-2 mL of KH-590 and 20-40 mL of TEOS.
[0014] Preferably, the dosage of each component in step 2 is 10-20 mL of TPAOH, 5-10 mL of H 2 O, 0.1-0.3g NaOH and 2-4g Al 2 (SO 4 ) 3 18H 2 O.
[0015] Preferably, the crystallization process in step three is first crystallization at 100° C. for 48 hours and then crystallization at 170° C. for 24 hours.
[0016] Preferably, in step 4, the temperature for overnight drying is 100° C., the calcination temperature is 550° C., and the calcination time is 5 hours.
[0017] Preferably, in step 5, NH 4 NO 3 The concentration of the solution is 1 mol / L, Ni@NaZSM-5 molecular sieve and NH 4 NO 3 The ratio of the solution is 1g:15ml.
[0018] Preferably, in step 5, the oil bath temperature is 80° C., the stirring time is 4 h, the overnight drying temperature is 100° C., the calcination temperature is 550° C., and the calcination time is 5 h.
[0019] Preferably, the sieve in step six is sieved to 20-40 mesh for later use.
[0020] The metal Ni is used as the metal active component, (3-mercaptopropyl) trimethoxysilane is used as the organic complex, which is used to prevent the metal Ni from precipitating under the high temperature and high alkalinity environment during the crystallization process of the molecular sieve, tetraethyl orthosilicate (TEOS) is used as the silicon source, and Al 2 (SO 4 ) 3 18H 2 O is the aluminum source, and tetrapropylammonium hydroxide (TPAOH) is used as the template. During the synthesis process, under the action of the organic ligand, the active component Ni is encapsulated in the microporous structure of the molecular sieve, thereby improving the metal dispersion, anti-sintering and anti-carbon deposition performance for the catalyst itself, and effectively improving the activity and stability of the catalyst; for the in-situ light-weighting process of tar, the spatial confinement characteristics of the molecular sieve are used to achieve the separation of the active sites of hydrogen-rich gas activation and tar cracking, and to achieve the matching of the number of hydrogen-rich small molecule free radicals and tar cracking fragments, thereby increasing the content and yield of light components in the tar.
[0021] Therefore, the present invention adopts the above-mentioned method for preparing an encapsulated metal catalyst for improving tar quality, which has the following beneficial effects:
[0022] (1) The present invention uses an organic silane coupling agent (3-mercaptopropyl) trimethoxysilane as a metal protective agent, which can effectively prevent the precipitation of metal Ni during the crystallization process under high alkalinity and high temperature conditions.
[0023] (2) The encapsulated Ni-based catalyst prepared by the present invention can reduce the agglomeration of Ni, make the metal Ni dispersed more evenly, and increase the effective activity and stability of the metal component Ni.
[0024] (3) The Ni@HZSM-5 molecular sieve catalyst prepared by the present invention and applied to the process of lightening coal pyrolysis tar effectively utilizes the hydrogen-rich gas in the pyrolysis system as a hydrogen source without the addition of external hydrogen, realizes the redistribution of hydrogen atoms in the pyrolysis products, avoids the metal active component Ni from participating in the activation of the hydrogen-rich gas and the cracking of the tar at the same time, and controls the activation of the hydrogen-rich gas by the amount of encapsulated metal Ni content, thereby generating free radical fragments to stabilize the light components in the tar.
[0025] (4) The Ni@HZSM-5 molecular sieve catalyst prepared by the present invention and used in the process of lightening coal pyrolysis tar is of great significance for the lightening of tar and the improvement of tar quality. It also provides a new way and idea for the directional regulation of substances in the process of lightening tar.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of a coal sample and a catalyst bed in an embodiment of a method for preparing an encapsulated metal catalyst for improving tar quality according to the present invention;
[0028] Figure 2 This is a TEM image of a catalyst in an embodiment of a method for preparing an encapsulated metal catalyst for improving tar quality according to the present invention;
[0029] Figure 3 This is a particle size analysis diagram of a catalyst in an embodiment of a method for preparing an encapsulated metal catalyst for improving tar quality according to the present invention;
[0030] Figure 4 is the H of different molecular sieve catalysts in the embodiment of the method for preparing an encapsulated metal catalyst for improving tar quality of the present invention. 2 -TPR analysis chart;
[0031] Figure 5 This is a tar analysis diagram under different catalysts in an embodiment of a method for preparing an encapsulated metal catalyst for improving tar quality of the present invention. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0033] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0034] Embodiment 1
[0035] The present invention provides a method for preparing an encapsulated metal catalyst for improving the quality of tar, wherein the metal is used as an active component, the active component metal is platinum, nickel, cobalt, molybdenum, etc., the carrier is a molecular sieve, and the mass fraction of the active component nickel is 1-5%. The organic complex (3-mercaptopropyl) trimethoxysilane KH-590 is used as a metal protective agent, tetraethyl orthosilicate TEOS is used as a silicon source, and Al 2 (SO 4 ) 3 18H 2O is an aluminum source, tetrapropylammonium hydroxide TPAOH is used as a template, and an encapsulated metal catalyst is prepared by encapsulating an active component in a molecular sieve during the crystallization process of the molecular sieve. During the synthesis process, under the action of an organic ligand, the active component Ni is encapsulated in the microporous structure of the molecular sieve, thereby improving the dispersion of the metal, the anti-sintering and anti-carbon deposition properties of the catalyst itself, and effectively improving the activity and stability of the catalyst; for the in-situ light-weighting process of tar, the spatial confinement characteristics of the molecular sieve are utilized to achieve the separation of active sites for hydrogen-rich gas activation and tar cracking, and to achieve the matching of the number of hydrogen-rich small molecule free radicals and tar cracking fragments, thereby increasing the content and yield of light components in the tar.
[0036] The specific steps include:
[0037] Step 1: First, take 10-20 mL of TPAOH and 5-10 mL of H 2 O and 0-2 mL of KH-590 were placed in a beaker and stirred for 8 h. Then, a certain concentration of Ni(NO 3 ) 2 6H 2 O solution and continue stirring for 0.5h, then slowly add 20-40mL of TEOS to the mixed solution and stir for 13h;
[0038] Step 2: Take 10-20 mL of TPAOH and 5-10 mL of H 2 O, 0.1-0.3g NaOH and 2-4g Al 2 (SO 4 ) 3 18H 2 O is prepared into a transparent solution, and then the prepared transparent solution is slowly added dropwise to the mixed solution in step 1, and then stirred in a water bath at 80°C for 2h to obtain a gel;
[0039] Step 3: After the obtained gel is loaded into an autoclave, it is crystallized in a homogeneous reactor at 100° C. for 48 hours and then at 170° C. for another 24 hours;
[0040] Step 4: centrifuge the crystallized catalyst to neutrality, dry it at 100°C overnight, and calcine the dried sample at 550°C in a muffle furnace for 5h to obtain a Ni@NaZSM-5 molecular sieve sample;
[0041] Step 5: Prepare 1 mol / L NH 4 NO 3 solution, Ni@NaZSM-5 molecular sieve and NH 4 NO 3The solution was stirred in an oil bath at 80°C for 4 h at a ratio of 1 g:15 ml. After filtration and washing, the same steps were repeated. The obtained catalyst was dried at 100°C overnight and calcined in a muffle furnace at 550°C for 5 h to obtain Ni@HZSM-5 molecular sieve.
[0042] Step 6: The obtained Ni@HZSM-5 molecular sieve is heated to 2 The catalyst was calcined at 700°C for 2h under a nitrogen atmosphere and pressed into tablets. The catalyst was crushed and sieved through 20-40 mesh to finally obtain the Ni@HZSM-5 molecular sieve catalyst, i.e., an encapsulated metal catalyst.
[0043] In the following examples, the coal sample is Inner Mongolia Baiyinhua lignite, and the tar upgrading process is carried out in a stainless steel tube fixed bed reactor with an inner diameter of 14 mm and a length of 290 mm ( Figure 1 ) is carried out, the reactor is a vertical two-layer structure, coal, quartz wool, catalyst, quartz wool are placed from top to bottom, a gas inlet is provided at the top of the reactor, and an outlet is provided at the bottom of the reactor. The liquid product produced by pyrolysis is N 2 The oil was brought into -20℃ cold hydrazine for cooling and collection, and the light oil content in the oil was obtained after simulated distillation analysis. The pyrolysis oil yield and light oil yield (dry ash-free basis) were calculated as follows:
[0044]
[0045] Light oil yield = oil product yield × light oil content
[0046] Among them, W 油品 is the oil quality; W 0 are the mass of coal sample; A ad is the ash content in coal; M ad It is the moisture in the coal.
[0047] Example 1
[0048] Catalyst preparation: Take 16.5 mL of TPAOH, 4.125 mL of H 2 O and 0.125mL KH-590 were placed in a beaker and stirred for 8 hours. Then, 3.27mL of 0.1mol / L nickel nitrate solution was added to the mixed solution and stirred for 0.5h. Then, 23.12ml of TEOS was slowly added dropwise to the mixed solution and stirred for 13h. 13.125mL of TPAOH, 6.75mL of H 2 O, 0.125 mL of NaOH and 1.381 g of aluminum sulfate were prepared into a transparent solution, which was slowly added dropwise to the previous mixed solution, stirred in a water bath at 80 °C for 2 h, and then loaded into a kettle.
[0049] Crystallization was carried out at 100 °C for 48 h and at 170 °C for 24 h in a homogeneous reactor. The obtained catalyst was centrifuged to neutrality, dried at 100 °C overnight, and then calcined at 550 °C in a muffle furnace for 5 h to obtain Ni@NaZSM-5 molecular sieve, denoted as 1Ni@NaZSM-5 molecular sieve. 1 mol / L NH 4 NO 3 The 1Ni@NaZSM-5 molecular sieve and ammonium nitrate solution were stirred in an 80°C oil bath at a ratio of 15 ml / g for 4 h. After filtration and washing, the same steps were repeated to dry the obtained catalyst at 100°C overnight. The 1Ni@HZSM-5 molecular sieve was calcined in a muffle furnace at 550°C for 5 h to obtain the obtained 1Ni@HZSM-5 molecular sieve. The obtained 1Ni@HZSM-5 molecular sieve was heated to 400 °C. 2 Calcine at 700℃ for 2h under atmosphere, press into tablets, crush and sieve to 20-40 mesh for later use.
[0050] The H 2 -TPR analysis such as Figure 4 shown.
[0051] Catalyst performance evaluation: Before the reaction, the catalyst was reduced and activated in a hydrogen atmosphere at 600°C for 1 h. The reaction temperature was 600°C and N 2 The flow rate was 300 mL / min, the heating furnace reached the specified temperature within 10 min and maintained for 30 min, the catalyst dosage was 1 g, the coal sample was 5 g, and the experiment was carried out in a fixed bed reactor. The results of Example 1 are shown in Figure 5 As shown, by comparing the oil yield, light oil content and yield of Example 1 and Comparative Example 1, it can be found that the tar yield of the Ni-based catalyst prepared by the encapsulation method is reduced to a certain extent compared with the non-catalytic pyrolysis experiment. This is because the acidity of the molecular sieve itself causes the cracking of the tar, and the content of light components in the tar is increased from 51.75wt.% to 72.60wt.%; the light oil yield is increased from 5.96wt.% to 6.97wt.%, an increase of 16.90%. This is because in the Ni-based catalyst prepared by the encapsulation method, Ni is mainly located in the pores of the molecular sieve, activating the hydrogen-rich components produced in the pyrolysis system, so that the free radicals produced by the heavy oil are more stabilized to form light oil, resulting in an increase in the yield of light oil in the tar.
[0052] Example 2
[0053] Catalyst preparation: Referring to Example 1, the difference between this example and Example 1 is that the Ni content in the Ni@HZSM-5 catalyst is 2 wt.%, expressed as 2Ni@HZSM-5.
[0054] The prepared 2Ni@HZSM-5 molecular sieve was observed by transmission electron microscopy, and the results are as follows Figure 2 , Figure 3 2Ni@HZSM-5 molecular sieve H 2 -TPR analysis such as Figure 4 shown.
[0055] Catalyst performance evaluation: Experimental conditions refer to Example 1. The oil yield, light oil content and yield before and after lightening by 2Ni@HZSM-5 catalyst are as follows: Figure 5 As shown. Compared with Example 1, the yield of tar is almost unchanged, but the light components in the tar are further increased, and the content of light components in the tar is increased from 72.60wt.% to 79.70wt.%; the yield of light oil products is increased from 6.97wt.% to 7.62wt.%, an increase of 9.30%. This is because as the content of encapsulated metal Ni increases, the amount of hydrogen-rich gas that can be activated also increases, further stabilizing the free radical fragments in the tar and increasing the light components in the tar. And through Figure 2 TEM images of the catalyst and Figure 3 The particle size analysis of the metal Ni shows that the prepared encapsulated Ni-based catalyst metal Ni has good dispersion, so it has good activity in activating hydrogen-rich gas. Figure 4 Different catalysts H 2 -TPR analysis shows that the interaction between the Ni-based catalyst prepared by the encapsulation method and the carrier is strong, and it is speculated that the metal Ni is in the internal pores of the molecular sieve.
[0056] Example 3
[0057] Catalyst preparation: Referring to Example 1, the difference between this example and Example 1 is that the Ni content in the Ni@HZSM-5 catalyst is 3 wt.%, expressed as 3Ni@HZSM-5.
[0058] The H 2 -TPR analysis such as Figure 4 shown.
[0059] Catalyst performance evaluation: Experimental conditions refer to Example 1. The oil yield, light oil content and yield before and after lightening by 3Ni@HZSM-5 catalyst are as follows: Figure 5 Compared with Example 2, the tar yield, the content of light oil in the tar and the yield do not change much, which may be because when the metal Ni content is 2%, the hydrogen-rich gas that can be activated has reached the upper limit. When the metal Ni content in the catalyst reaches 3%, the active sites reach a saturated state, so the tar yield, light oil content and yield are not greatly affected.
[0060] Comparative Example 1
[0061] The difference between this comparative example and Example 1 is that the reaction is carried out under non-catalytic conditions, and other experimental conditions refer to Example 1.
[0062] Comparative Example 2
[0063] Catalyst preparation: First, take 16.5 mL of TPAOH, 4.125 mL of H 2 O and 0.125 mL of KH-590 were placed in a beaker and stirred for 8 h. Then 23.12 mL of TEOS was slowly added dropwise to the mixed solution and stirred for 13 h. 13.125 mL of TPAOH, 6.75 mL of H 2 O, 0.125 mL of NaOH and 1.381 g of Al 2 (SO 4 ) 3 18H 2 O was prepared into a transparent solution, and the prepared transparent solution was slowly added to the previous mixed solution and stirred in a water bath at 80°C for 2h. After the obtained gel was transferred into the reactor, it was crystallized in a homogeneous reactor at 100°C for 48h, and then at 170°C for 24h. The catalyst obtained after crystallization was centrifuged and washed to neutrality and dried at 100°C overnight. The dried sample was calcined at 550°C in a muffle furnace for 5h to obtain a NaZSM-5 molecular sieve sample. 1 mol / L NH 4 NO 3 Solution, ammonium nitrate solution and NaZSM-5 molecular sieve at a ratio of 15 ml / g are stirred in an 80 ° C oil bath for 4 hours. After filtration and washing, the same steps are followed again. The obtained catalyst is dried at 100 ° C overnight and calcined at 550 ° C in a muffle furnace for 5 hours to obtain HZSM-5 molecular sieve.
[0064] First, weigh 1.011 g of Ni(NO 3 ) 2 6H 2 O and 10g of the HZSM-5 molecular sieve prepared above were placed in a 250mL beaker, water was added to the beaker to about 180mL, and stirred for four hours. After stirring, a rotary evaporator was used to remove most of the solvent in the mixed solution, and then dried in an oven at 100°C for 10h, and then calcined in a muffle furnace at 550°C for 5h, and then heated in H 2 The catalyst was calcined at 550 °C for 5 h under a nitrogen atmosphere for reduction activation, and finally a 2Ni / HZSM-5 catalyst was obtained.
[0065] The H 2 -TPR analysis such as Figure 4 shown.
[0066] Catalyst performance evaluation: Experimental conditions refer to Example 1. The oil yield, light oil content and yield before and after lightening by 2Ni / HZSM-5 catalyst are as follows: Figure 5 The experiment found that compared with the Ni-based catalyst prepared by encapsulation, the 2Ni / HZSM-5 molecular sieve catalyst further reduced the yield of tar. Although the content of light oil in the tar increased from 79.70wt.% of the 2Ni@HZSM-5 molecular sieve to 84.56wt.%, the overall yield of light oil decreased from 7.62wt.% to 6.88wt.%. This may be because the impregnated metal Ni is on the outer surface of the molecular sieve, which participates in the aggravation of the tar cracking process, resulting in a decrease in the tar yield. This can be seen from the Figure 4 The corresponding conclusions were obtained by comparing the H2-TPR analysis of different catalysts, and the reaction results were consistent with the concept of the present invention.
[0067] Therefore, the present invention adopts the above-mentioned method for preparing an encapsulated metal catalyst for improving the quality of tar. This method solves the problems of traditional supported catalyst metal participating in the tar cracking process, causing excessive cracking of tar and low light oil yield, and is of great significance for improving the quality of tar and solving the problems of quantitatively controlling the tar cracking products.
[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing an encapsulated metal catalyst for improving the quality of tar, wherein the metal is used as an active component, an organic complex (3-mercaptopropyl) trimethoxysilane KH-590 is used as a metal protective agent, tetraethyl orthosilicate TEOS is used as a silicon source, Al2(SO4)3·18H2O is used as an aluminum source, and tetrapropylammonium hydroxide TPAOH is used as a template agent. The active component is encapsulated in a molecular sieve during the crystallization process of the molecular sieve to prepare an encapsulated metal catalyst, wherein: The following steps are involved: Step 1: First, take a certain amount of TPAOH, H2O and KH-590 into a beaker, mix and stir for 8 hours, then add a certain amount of Ni(NO3)2·6H2O solution into the mixed solution and continue stirring for 0.5 hours, then slowly add a certain amount of TEOS into the mixed solution and stir for 13 hours; Step 2: prepare a transparent solution with a certain amount of TPAOH, H2O, NaOH and Al2(SO4)3·18H2O, then slowly drop the prepared transparent solution into the mixed solution of step 1 and stir in a water bath at 80°C for 2h to obtain a gel; Step 3, after the obtained gel is loaded into an autoclave, it is crystallized in a homogeneous reactor; Step 4: centrifuge the catalyst obtained after crystallization to neutrality, dry overnight, and calcine the dried sample in a muffle furnace to obtain a Ni@NaZSM-5 molecular sieve sample; Step 5: Prepare NH4NO3 solution, stir the Ni@NaZSM-5 molecular sieve and NH4NO3 solution in an oil bath, filter and wash, and repeat the same steps, dry the obtained catalyst overnight, and calcine in a muffle furnace to obtain Ni@HZSM-5 molecular sieve; Step 6: calcine the obtained Ni@HZSM-5 molecular sieve at 700°C for 2h under H2 atmosphere and press into tablets, crush and sieve to finally obtain Ni@HZSM-5 molecular sieve catalyst, i.e., encapsulated metal catalyst.
2. The method for preparing an encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The mass fraction of the active component metal nickel is 1%-5%.
3. The method for preparing an encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The active component metal is platinum, nickel, cobalt, molybdenum, etc., and the carrier is a molecular sieve.
4. The method for preparing an encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The dosage of each component in the step 1 is: 10-20 mL of TPAOH, 5-10 mL of H2O, 0-2 mL of KH-590 and 20-40 mL of TEOS.
5. The method for preparing an encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The dosage of each component in the step 2 is 10-20 mL of TPAOH, 5-10 mL of H2O, 0.1-0.3 g of NaOH and 2-4 g of Al2(SO4)3·18H2O.
6. The method for preparing an encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The crystallization process in step 3 is to first crystallize at 100° C. for 48 hours and then crystallize at 170° C. for 24 hours.
7. The method for preparing an encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: In the step 4, the temperature for overnight drying is 100° C., the calcination temperature is 550° C., and the calcination time is 5 hours.
8. The method for preparing an encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: The concentration of the NH4NO3 solution in step 5 is 1 mol / L, and the ratio of the Ni@NaZSM-5 molecular sieve to the NH4NO3 solution is 1 g:15 ml.
9. The method for preparing an encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: In the step 5, the oil bath temperature is 80° C., the stirring time is 4 hours, the overnight drying temperature is 100° C., the calcination temperature is 550° C., and the calcination time is 5 hours.
10. The method for preparing an encapsulated metal catalyst for improving tar quality according to claim 1, characterized in that: In step 6, the mixture is sieved to 20-40 mesh for later use.
Citation Information
Patent Citations
Method for increasing tar yield by coupling aromatization of hydrocarbons with coal pyrolysis
CN102161904A
Molecular sieve catalyst for catalytic cracking of MTP (methanol to propylene) by-product hydrocarbons and preparation method of molecular sieve catalyst
CN106669790A
Preparation and application of ZnCo-based bimetallic catalyst of Silicalite-1 molecular sieve micropore channel confinement
CN112844445A
In-situ preparation method of high-stability molecular sieve supported metal catalyst
CN113751055A
Preparation method and application of noble metal-coated macroporous-mesoporous-microporous molecular sieve catalyst
CN117225462A
